Pengaruh Konseling Kelompok Teknik WDEP (Wants Direction Evaluation Planning) Terhadap Peningkatan Perilaku Tanggung Jawab dalam Penyelesaian Tahfidz - Sabrina Khairunnisa; Tawil Tawil; Paramita Nuraini (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of group counseling with the WDEP technique onincreasing responsible behavior in completing tahfid.The research method is quantitative. The type of this research is experimental research.The design of this research uses Pre-Experimental One Group Pretest Posttest. The subjectof this research is class 2E MTs Muhammadiyah 02 Patean Kendal totaling 30 students.Sampling. The data collection method is using a questionnaire. Data analysis is using thePaired Sample T-Test.The conclusion of this study is that group counseling with the WDEP technique has noeffect on increasing responsible behavior in the completion of low tahfid. The significanceresults show 0.37 more than 0.05, so it can be concluded that Ho is accepted, Ha is rejected,meaning that group counseling with the WDEP technique has no effect on increaseresponsibility in completing tahfid after being given treatment using group counselingservices with the WDEP technique. The reasons the results of this study have no effect areas follows; the time used for counseling services at night during the night and virtualbreaks and, and also the time limited by the cottage or the place used for research due tothe effects of this pandemic.